The Impact of Using Certified Durian Seedlings on Durian Farming Income in Amoito Village, Ranomeeto Sub-district - Ayuba Destanty; La Ode Alwi; Hadi Sudarmo (International journal of technology and education research, 2025)
The durian tree in Amoito Village is a local and superior type of durian tree. If the more characteristics that consumers like are collected in one fruit, the higher the economic value (price) of the fruit. Thus it can be classified as a superior fruit. For this reason, examples of how to assess durian fruit can be taken based on the criteria for the appearance of the fruit and the characteristics of the fruit that consumers like. This research was carried out in Amoito Village, Ranomeeto District. From January to March 2024, the research location was determined purposively, where the area was one of the villages in Ranomeeto District whose people cultivated durian farming. The population in this study were all farmers who cultivated durian, namely 30 people. Determining the sample in this study used a saturated sampling technique, where the entire population was sampled. There were 19 samples from farmers who used certified seeds and 11 from farmers who used non-certified seeds. Farming businesses using certified seeds earned the highest income compared to farming businesses using non-certified seeds. This is because certified durian seed farming produces higher yields compared to non-certified ones. The results of farming certified durian seeds are Rp. 314,415,000 while non-certified durian seed farming is Rp. 177,713,709.53. The total income of farmers who use certified and non-certified seeds is IDR. 196,701,291 which means positive impact (+). Where the income received by farmers who use certified seeds is greater than non-certified